The Influence of Self Service Technology on Passenger Satisfaction at General Ahmad Yani International Airport Semarang - Benny Michael Sihombing; Septiyani Putri Astutik (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
PT. Angkasa Pura I as the manager of Semarang General Ahmad Yani International Airport always strives to improve its services which is manifested by self-service. Self service technology is used to serve passenger check-in independently so it is very easy to use and saves time. The conveniences provided by implementing self-check-in are certainly very influential on passenger satisfaction. This study used a quantitative method by distributing questionnaires. The questionnaire in this study was distributed to all passengers at General Ahmad Yani International Airport in Semarang with a total of 100 respondents. This study used data analysis techniques, namely instrument testing, classical assumption testing, simple regression analysis and hypothesis testing. The results of this study are that there is an effect of self-service technology on passenger satisfaction at Jenderal Ahmad Yani International Airport, Semarang. This is reinforced by the results of the calculation of the coefficient of determination where R is 0.893 with R2 of 79.7%.